Re-understanding media : feminist extensions of Marshall McLuhan - Sharma, Sarah, 1977-; Singh, Rianka, 1991- (Duke University Press, 2022)
"The contributors to Re-Understanding Media advance a feminist version of Marshall McLuhan's key text, Understanding Media: The Extensions of Man, repurposing his insight that "the medium is the message" for feminist ends. They argue that while McLuhan's theory provides a falsely universalizing conception of the technological as a structuring form of power, feminist critics can take it up to show how technologies alter and determine the social experience of race, gender, class, and sexuality. This volume showcases essays, experimental writings, and interviews from media studies scholars, artists, activists, and those who work with and create technology. Among other topics, the contributors extend McLuhan's discussion of transportation technology to the attics and cargo boxes that moved Black women through the Underground Railroad, apply McLuhan's concept of media as extensions of humans to analyze Tupperware as media of containment, and take up 3D printing as a feminist and decolonial practice. The volume demonstrates how power dynamics are built into technological media and how media can be harnessed for radical purposes."--